2009
DOI: 10.1186/1465-9921-10-126
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting toll-like receptor 4 signaling ameliorates pulmonary fibrosis during acute lung injury induced by lipopolysaccharide: an experimental study

Abstract: BackgroundToll-like receptor 4 (TLR4) is essential in lipopolysaccharide (LPS)-induced fibroblast activation and collagen secretion in vitro. However, its effects on the process of lung fibroblast activation and fibrosis initiation during LPS induced acute lung injury (ALI) remain unknown. The goal of the present study was to determine the effect of inhibiting TLR4 on LPS-induced ALI and fibrosis in vivo.MethodsThe ALI model was established by intraperitoneal injection of LPS in mice. TLR4-small hairpin RNA (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
65
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 29 publications
9
65
0
Order By: Relevance
“…Previous studies have shown that TLR4 is required for LPS-associated lung fibroblast activation 12 and proliferation, 14,17 lung inflammatory reaction, 18,19 and pulmonary fibrosis. 1 In agreement with these published findings, our present study demonstrated that upregulation of TLR4 by LPS accounted for LPS-induced proliferation in mouse lung fibroblasts (MIC-CELL-0040) that could be restored by siRNA-mediated TLR4 silencing, suggesting that TLR4 is essential for LPS-induced Thy-1 gene silencing in lung fibroblasts and cell proliferation. Further experiments are needed to confirm the role of TLR4 in lung fibroblast proliferation with TLR4 knockout cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have shown that TLR4 is required for LPS-associated lung fibroblast activation 12 and proliferation, 14,17 lung inflammatory reaction, 18,19 and pulmonary fibrosis. 1 In agreement with these published findings, our present study demonstrated that upregulation of TLR4 by LPS accounted for LPS-induced proliferation in mouse lung fibroblasts (MIC-CELL-0040) that could be restored by siRNA-mediated TLR4 silencing, suggesting that TLR4 is essential for LPS-induced Thy-1 gene silencing in lung fibroblasts and cell proliferation. Further experiments are needed to confirm the role of TLR4 in lung fibroblast proliferation with TLR4 knockout cells.…”
Section: Discussionsupporting
confidence: 92%
“…1,2 The phenotypic transition of lung fibroblasts during the process of pulmonary fibrosis can be stimulated by various pathological conditions, including lipopolysaccharide (LPS), a component of bacteria membranes and an important player during the development of pulmonary fibrosis. 3,4 LPS-induced proliferation of lung fibroblast is associated with the silencing of thymocyte differentiation antigen-1 (Thy-1) and deacetylation of histones H3 and H4 at the Thy-1 gene promoter; 5,6 however, the mechanism by which LPS promotes the deacetylation of histones H3 and H4 leading to downregulation of Thy-1 gene expression is largely unknown.…”
mentioning
confidence: 99%
“…3,5,28 Our finding that HMGB1 can enhance LPSinduced lung fibroblast proliferation is novel, yet consistent with findings of cooperative effects in other types of cells, including synovial fibroblasts, macrophages, and human monocytes. [29][30][31] For example, Wahamaa et al 32 showed that HMGB1 increased LPS-induced secretion of cytokines, such as tumor necrosis factor-α (TNF-α), interleukin (IL)-6, and IL-8, in synovial fibroblasts.…”
Section: Discussionsupporting
confidence: 85%
“…HMGB1 activates inflammatory pathways by stimulating TLR4 in many types of tissue injuries. 42,43 Our previous work, [22][23][24] as well as the work of others, [25][26][27] indicated that TLR4 mediates many forms of ALI, such as hemorrhagic shock-induced ALI and LPS-induced ALI. Overexpression of TLR4 in the lung tissue amplifies the severity of LPS-induced ALI.…”
Section: Discussionmentioning
confidence: 94%
“…[19][20][21] We have previously demonstrated that the activation of TLR4 and its downstream intracellular signal-transduction pathways is crucial to lipopolysaccharide (LPS)-induced ALI. [22][23][24] Other studies also reported that TLR4 mutant (C3H/HeJ) mice developed less ALI after unresuscitated hemorrhagic shock or being challenged with LPS. 25,26 Conversely, the overexpression of TLR4 in transgenic mice aggravated ALI and pulmonary inflammation, endothelial cell damage, and the recruitment of neutrophils to the lung.…”
mentioning
confidence: 95%